Fall determinants and home modifications by occupational therapists to prevent falls: Facteurs déterminants des chutes et modifications du domicile effectuées par les ergothérapeutes pour prévenir les chutes. (February 2018) - Maggi, Patrick; de Almeida Mello, Johanna; Delye, Sam; Cès, Sophie; Macq, Jean; Gosset, Christiane; Declercq, Anja
Background: Approximately one third of older people over 65 years fall each year. Home modifications may decrease occurrence of falls. Purpose: This study aims to determine the risk factors of falls for frail older persons and to evaluate the impact of home modifications by an occupational therapist on the occurrence of falls. Method: We conducted a longitudinal study using a quasiexperimental design to examine occurrence of falls. All participants 65 years of age and older and were assessed at baseline and 6 months after the intervention. Bivariate analysis and logistic regression models were used to study the risk factors of falls and the effect of home modifications on the incidence of falls. Findings: The main predictors of falls were vision problems, distress of informal caregiver, and insufficient informal support. Home modifications provided by an occupational therapist showed a significant reduction of falls. Implications: Informal caregivers and their health status had an impact on the fall risk of frail older persons. Home modifications by an occupational therapist reduced the fall risk of frail older persons at 6-months follow-up.